PENGARUH LINGKUNGAN KERJA NON FISIK, DISIPLIN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI PERWAKILAN BKKBN PROVINSI SULAWESI TENGGARA - Darisman Paeha; Adnan Hakim; Wahyuniati Hamid; Dedy Takdir Syaifuddin (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to determine: (1). the influence of the non-physical work environment on work discipline, (2) the influence of the non-physical work environment on organizational commitment, (3) the influence of the non-physical work environment on employee performance, (4) the influence of work discipline on employee performance, (5) the effect of organizational commitment on employee performance, (6). the role of work discipline as a mediation of the influence of the non-physical work environment on employee performance and (7). the role of organizational commitment as mediating the influence of the non-physical work environment on employee performanceThe study population was 57 people and the entire population was sampled. The analytical tool used is Partial Least Square (PLS) with Smart-PLS version 3.2.4 . program. The results showed that (1). The non-physical work environment has a positive and significant effect on work discipline, (2) The non-physical work environment has a positive and significant effect on organizational commitment, (3) The non-physical work environment has a positive and significant effect on employee performance, (4) Work discipline has a positive and significant effect on organizational commitment. significant effect on employee performance, (5) organizational commitment has a positive and significant effect on employee performance, (6). Work discipline acts as a mediation of the influence of the non-physical work environment on employee performance and (7). Organizational commitment acts as a mediation of the influence of the non-physical work environment on employee performance